Pre-flight performance of the ion energy mass spectrum analyzer for the Martian Moons eXploration (MMX) mission - Shoichiro Yokota; Ayako Matsuoka; Naofumi Murata; Yoshifumi Saito; Kazushi Asamura; Satoshi Kasahara; Dominique Delcourt; Lina Z. Hadid; Naoki Terada; Kunihiro Keika; Yuki Harada; Hiromu Nakagawa; et al. (Progress in Earth and Planetary Science)
Abstract An ion energy mass spectrum analyzer was developed for the Martian Moons eXploration (MMX) mission to measure the three-dimensional velocity distribution function and mass profile of low-energy ions around the Mars-Moon system. The hemispheric field-of-view (FOV) is acquired by a pair of angular scanning deflectors, and the energy/charge and mass/charge are determined for each ion by an electrostatic analyzer and a linear-electric-field (LEF) time-of-flight (TOF) analyzer, respectively, with an enhanced mass resolution of $$m/\Delta m\sim 100$$ m / Δ m ∼ 100 . The ion analyzer, together with magnetometers, constitutes the mass spectrum analyzer (MSA), one of the scientific instruments on board the MMX spacecraft. This paper describes the instrumentation of the ion analyzer, and results of the performance tests of its flight model (FM).